Pengaruh Pemberian Iba (Indole Butyric Acid) dan Konsentrasi Naa (Naphthalene Acetic Acid) terhadap Keberhasilan Penyetekan Sirih Merah (Piper Crocatum Ruiz and Pav.) - Desi Maulida; Rugayah Rugayah; Dewi Andalasari (Politeknik Negeri Lampung., 2013)
The research was conducted at the cutting red betel (Piper crocatum Ruiz and Pav.) to determined the effect of (1) the difference growth of cuttings of red betel which are given IBA and without IBA, (2) the concentration of NAA on growth of cutting red betel, (3) the concentration of NAA on growth of cutting red betel on each given IBA. The treatment was arranged in factorial (2 x 4) in randomized block design with three replication. The first factor were without IBA (a0) and the given of 1.000 ppm IBA (a1). The second factor were the concentration of NAA consists of: 0 ppm (b0), 1.000 ppm (b1), 2.000 ppm (b2), and 4.000 ppm (b3). The results showed that the NAA concentration of 4000 ppm produced the most number of roots on either at the node or at the base of cutting. Planting cutting red betel which given IBA 1.000 ppm was able to accelerated the time leaves open and increased the number of cutting which germinate. The mixtured of giving IBA 1.000 ppm and the concentration of NAA 4.000 ppm, produced the most number of cutting that germinated. Keywords : red betel, given IBA, dan concentration NAA